Design of Using Activity Based Budgeting Methods for Controlling Employee Overtime Costs - Novita Sari, Mega; Nengzih, Nengzih (Riviera Publishing, 2023)
This study aims to design and propose using overtime budgets in companies. This type of research is descriptive exploratory, and the research object is data related to employee overtime in July-December 2021. The financing method used is time-driven activity-based costing (TDABC). This study suggests that companies follow up on departments with over-capacity status to evaluate employee activities during overtime so that it does not affect company performance. The application of the activity-based budgeting method can increase the effectiveness of employee overtime costs because it can prove that there are savings in overtime costs and can increase profits. So that the ABB method can control the overtime budget more efficiently and better. The ABB method can control employee overtime budgets more efficiently. The ABB method can be proposed to companies to control their employees' overtime costs. This research has implications for identifying the need for overtime, purchasing efficient budget allocations, evaluating the impact on financial companies.